1998
DOI: 10.1073/pnas.95.21.12719
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a oxygenase ( CAO ) is involved in chlorophyll b formation from chlorophyll a

Abstract: Chlorophyll b is an ubiquitous accessory pigment in land plants, green algae, and prochlorophytes. Its biosynthesis plays a key role in the adaptation to various light environments. We isolated six chlorophyll b-less mutants by insertional mutagenesis by using the nitrate reductase or argininosuccinate lyase genes as tags and examined the rearrangement of mutant genomes. We found that an overlapping region of a nuclear genome was deleted in all mutants and that this encodes a protein whose sequence is similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
242
0
7

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 398 publications
(259 citation statements)
references
References 26 publications
10
242
0
7
Order By: Relevance
“…POR catalyzes the light-dependent reduction of protochlorophyllide a to chlorophyllide a, which is subsequently converted into chlorophyllide b by CAO [56][57][58][59]. The Arabidopsis genome has a single-copied CAO gene and three structurally related POR genes (A, B and C), of which only PORB is expressed throughout most developmental Cell Research | www.cell-research.com…”
Section: Chlorophyll Biosynthesis Is Downregulated In Spc1mentioning
confidence: 99%
“…POR catalyzes the light-dependent reduction of protochlorophyllide a to chlorophyllide a, which is subsequently converted into chlorophyllide b by CAO [56][57][58][59]. The Arabidopsis genome has a single-copied CAO gene and three structurally related POR genes (A, B and C), of which only PORB is expressed throughout most developmental Cell Research | www.cell-research.com…”
Section: Chlorophyll Biosynthesis Is Downregulated In Spc1mentioning
confidence: 99%
“…For this purpose, we identi®ed the gene involved in Chl b biosynthesis in Chlamydomonas reinhardtii (Tanaka et al, 1998). The gene encoded a novel oxygenase with a Rieske-type [2Fe-2S] cluster and a mononuclear iron-binding site.…”
Section: Introductionmentioning
confidence: 99%
“…The Arabidopsis genome encodes five Riesketype oxygenases (Gray et al, 2004), all of which have been shown to localize to chloroplasts (Rathinasabapathi et al, 1997;Tanaka et al, 1998;Bartsch et al, 2008). In addition, three of them, PAO (At3g44880), TIC55 (At2g24820), and PTC52 (At4g25650), possess predicted C-terminally located transmembrane domains ( Figure 5A) that likely anchor these proteins to plastid membranes, while the other two Rieske-type oxygenases in Arabidopsis, chlorophyll a oxygenase (At1g44446) and choline monooxygenase (CMO)-like (At4g29890) are predicted to be soluble proteins (Tusnády and Simon, 2001).…”
Section: Hydroxy-pfcc Is Present In Gerontoplasts Of Arabidopsismentioning
confidence: 99%